Impact of meningococcal C conjugate vaccination programs with and without catch-up campaigns in adolescents: Lessons learned from Bahia, Brazil - Lara Evellyn do Macedo; Viviane Matos Ferreira; Caroline Alves Feitosa; Amélia Maria Pithon Borges Nunes; Leila Carvalho Campos; Marco Aurélio Palazzi Sáfadi (Taylor & Francis Group, 2018)
The significant increase in the incidence rates and ongoing outbreaks of serogroup C meningococcal (MenC) disease, associated with the sequence type-103 complex, motivated the incorporation of the meningococcal C conjugate (MCC) vaccine in the routine immunization program in the State of Bahia, Brazil in early 2010, targeting children younger than 5 years of age. In its capital, Salvador, the program also included a catch-up campaign for individuals 10-24 years of age. We performed an observational, ecological study, analyzing data collected from 2007 to 2015, to compare the impact of these two immunization strategies on meningococcal disease incidence and mortality rates. In Salvador, following the vaccination program, a dramatic early impact on MenC disease and mortality rates could be observed, with significant reductions in incidence rates of MenC disease in all age groups, including individuals that were too old to have been vaccinated, indicating the presence of herd protection. Compared to the pre-vaccine period, a virtual disappearance of MenC disease was observed in 2015. However, in the state of Bahia (excluding the city of Salvador), no herd protection could be observed, with significant impact only among vaccine-eligible children within 5 years of introduction of the MCC vaccination program. These results highlight the importance of catch-up campaigns, including adolescents and young adults, to induce herd protection compared to immunization strategies restricted to infants and young children. This information is crucial for identifying optimal immunization policies and future strategies, focused on adolescents, to optimize the impact of MCC vaccination programs.